Estudo comparativo entre a sutura contínua e a com pontos separados na parede abdominal de ratos - Tognini, João Ricardo F. (1997)
The purpose of the experiment was to compare the continuous and interrupted techniques of abdominal clousure. It was used 48 male rats Wistar to realize longudinal laparotomies with a standardized technique. In 24 of them, the abdominal wall was closed by continuous suture and in 24 of them closed by interrupted suture. All of them using polidioxanone. In the 7th and 14th postoperative day, 12 animals of each group were submitted to euthanasia and the front abdominal wall was removed (without skin) and divided in two segmentes (cranial and caudal), one for hystological analysis with an objective measurament og collagenous and another to the test of tensile strength by tensiometer. The resultant data were submitted to statistical analysis. It was conclued that in the 7th day , the abdominal wall closed by interrupted technique is more resistant without significant diferences on collagenous density than the other closed by interrupted, and at the 14th day the results are similar, in rats.